2017
DOI: 10.1002/qj.3120
|View full text |Cite
|
Sign up to set email alerts
|

Large‐eddy simulation of vortex streets and pollutant dispersion behind high‐rise buildings

Abstract: Understanding turbulent flow and pollutant dispersion in urban areas is one of the important problems in urban meteorology and environmental fluid mechanics. In this study, we examine turbulent flow and pollutant dispersion in a densely built‐up area in Seoul, South Korea, using the parallelized large‐eddy simulation model (PALM). In particular, we focus on vortex streets and associated pollutant dispersion behind high‐rise buildings. The turbulence recycling method is used to produce inflow profiles. Vortices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…The power spectra showed a peak at normalized frequency 0.2-0.3, indicating the vortices are oscillated approximately at this frequency. This frequency is similar to the result reported by Han et al [49] in a LES simulation of urban flows with tall buildings. The coherent vortex motion contributes to the TKE and momentum flux transport of at the lee side of the tall building [49], which is also evident in our flowing TKE and turbulent momentum flux analysis.…”
Section: Karman Vortex Street Generated By the Tall Buildingssupporting
confidence: 91%
See 2 more Smart Citations
“…The power spectra showed a peak at normalized frequency 0.2-0.3, indicating the vortices are oscillated approximately at this frequency. This frequency is similar to the result reported by Han et al [49] in a LES simulation of urban flows with tall buildings. The coherent vortex motion contributes to the TKE and momentum flux transport of at the lee side of the tall building [49], which is also evident in our flowing TKE and turbulent momentum flux analysis.…”
Section: Karman Vortex Street Generated By the Tall Buildingssupporting
confidence: 91%
“…This frequency is similar to the result reported by Han et al [49] in a LES simulation of urban flows with tall buildings. The coherent vortex motion contributes to the TKE and momentum flux transport of at the lee side of the tall building [49], which is also evident in our flowing TKE and turbulent momentum flux analysis. The capability to simulate these coherent vortices in the flow is important in building structure design [50] and in transport and dispersion modeling applications.…”
Section: Karman Vortex Street Generated By the Tall Buildingssupporting
confidence: 91%
See 1 more Smart Citation
“…Past research in urban atmospheric problems has shown that coupling may exist between atmospheric airflow at the city scale (O(10 km)), neighbourhood scale (O(1 km)), and street scale (O(0.1 km)) (Barlow et al 2017;Fernando 2010). This spatial coupling effect is par-ticularly strong around urban forms such as groups of tall buildings (Han et al 2017;Fuka et al 2018;Hertwig et al 2019), or around steep topographic changes. To understand the importance of coupling effects we require a mapping between urban morphology and flowfield characteristics, such as mean velocity, turbulent statistics, momentum and heat fluxes.…”
Section: Introductionmentioning
confidence: 99%